2004
DOI: 10.1211/0022357043923
|View full text |Cite
|
Sign up to set email alerts
|

Lack of effect of proteinase-activated receptor-2 (PAR-2) deletion on the pathophysiological changes produced by lipopolysaccharide in the mouse: comparison with dexamethasone

Abstract: This study tested the hypothesis that activation of proteinase-activated receptor-2 (PAR-2) contributes towards the pathophysiology of lipopolysaccharide (LPS)-induced shock in the mouse. The effects of LPS on plasma glucose, biochemical markers of hepatic, renal and pancreatic exocrine function and lung content of myeloperoxidase (MPO) were examined in homozygous PAR-2 knockout mice (PAR-2 -/-) and genetically equivalent, homozygous PAR-2 +/+ mice. The effect of LPS was also examined in normal mice receiving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Pawlinski and colleagues [110] demonstrated that the deficiency of PAR 1 or PAR 2 alone did not affect mouse survival in a model of endotoxemia. The lack of any significant effect of the PAR 2 deficiency at the pathophysiological changes induced by LPS in the mouse was also confirmed in the work of Kazerani and coauthors [111]. However, an application of hirudin (a thrombin inhibitor) in PAR 2 knockout mice protected these animals better than PAR 2 wild-type mice against LPS-induced lethality [110].…”
Section: Pars and Endotoxemia Modelsmentioning
confidence: 71%
“…Pawlinski and colleagues [110] demonstrated that the deficiency of PAR 1 or PAR 2 alone did not affect mouse survival in a model of endotoxemia. The lack of any significant effect of the PAR 2 deficiency at the pathophysiological changes induced by LPS in the mouse was also confirmed in the work of Kazerani and coauthors [111]. However, an application of hirudin (a thrombin inhibitor) in PAR 2 knockout mice protected these animals better than PAR 2 wild-type mice against LPS-induced lethality [110].…”
Section: Pars and Endotoxemia Modelsmentioning
confidence: 71%
“…In agreement with this, PAR-2-deficient mice, compared with wild-type animals, showed lowered leukocyte rolling and reduced content of myeloperoxidase, a neutrophil marker. This was seen after surgical trauma and LPS-induced damage, respectively (35,43).…”
Section: Discussionmentioning
confidence: 91%
“…Endotoxaemia also leads to hepatocellular injury and dysfunction. Consequently, an elevation of the serum ALT levels has been reported in different studies [14,23]. Furthermore, LPS increases serum creatinine and bilirubin as a result of renal damage [14,23].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, an elevation of the serum ALT levels has been reported in different studies [14,23]. Furthermore, LPS increases serum creatinine and bilirubin as a result of renal damage [14,23]. Similarly, systemic LPS is associated with acute pancreatic damage/dysfunction [24], and different studies indicate accompanied increases in serum lipase levels [14,23,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation